CHALICE head injury rule: an implementation study. Issue 10 (20th July 2010) - Harty, E; Bellis, F
Abstract : Introduction: Paediatric head injury is a common presentation to emergency departments (ED), and the 2007 National Institute for Health and Clinical Excellence head injury guidelines included a paediatric section to deal with this. This is based on the Children's Head Injury Algorithm for the Prediction of Important Clinical Events (CHALICE) head injury rule. To date, no studies have examined the impact of the guideline on ED resources. Method: The 2007 guideline criteria were applied to records of patients seen pre-2007. By comparing the number of scans done with these criteria with those done in actual practice, the resource implications of the 2007 guideline could be assessed. Results: If the pre-existing (2003) guideline had been strictly applied, 28 (6%) of the 464 patients analysed would have received a computed tomography (CT) scan. Applying the 2007 guideline to the same 464 patients resulted in an extra 21 (4.6%) scans. Discussion: The cost effect of an extra 21 CT scans per annum is estimated at £3570. This is offset against a potential cost saving on admissions of £10 450. The neoplasia risks of increased scanning are also discussed. Problems in this study were the preference for admission over scanning in children who qualified for scan under both guidelines and absent data from clinical records. Further work could include a prospective study of the guideline.